Legal Liability of Advocates in Legal Services Contracts - Mohammad Zamroni (Susbtantive Justice International Journal of Law, 2020)
The main role of an advocate is to help clients get a fair legal process. This role gives birth to high expectations of advocates so that clients give full confidence to advocates to represent their interests. But in practice, it is not uncommon for advocates to abuse the trust given by their clients. As recorded in the 2019 PERADI annual report which shows that advocates reported by their clients to the PERADI Honorary Board are increasing. Avocados do have immunity rights as regulated in Article 16 of Law No. 18 of 2003 concerning Advocates jo. the decision of the Constitutional Court through decision No. 26 / PUU-XI / 2013. But of course, advocates cannot always protect their immune rights, especially if advocates violate the law and harm the interests of their clients. This study aims to analyze the legal responsibilities of lawyers who violate the law while carrying out their profession and are bound in a legal services contract. This research is normative legal research. The approach used in this research is the conceptual approach, the legislation approach, and the case approach. This research concludes that even though law violations were carried out by lawyers while carrying out their profession and based on a contract, advocates remain responsible, both civil and criminal. While the right to immunity can only be used as a basis for legal protection when advocates in good faith in defending the interests of their clients.